Robust H∞ Control for the Spacecraft with Flexible Appendages - Aiping Pang; Hui Zhu; Junjie Zhou; Zhen He; Jing Yang (Complexity)
Aiming at the oscillation suppression of spacecraft with large flexible appendages, we propose a control strategy using H∞ control. The weighting functions are designed for the specific flexible modes of the spacecraft and the frequency of harmonic interference in its operating environment. Taking into account the structural uncertainty of systematic modeling and the comprehensive performance requirements of system bandwidth constraint and attitude stability, the H∞ comprehensive performance matrix is constructed. A space telescope with a large flexible solar array is presented as an illustrative example, and a control design that meets the requirement for pointing accuracy is proposed. The simulation results show that the designed controller satisfies the requirements of attitude stability and high pointing accuracy and has effectively suppressed the disturbance of endemic frequency. The design scheme and selection method of the weight function shown in this paper can be a reference for the controller design for oscillation suppression of this type of spacecraft with flexible structures.